Analysis Of Post Sectio Caesarea Nursing Care Using Benson's Relaxation Technique to Reduce Pain: Case Study - Puspita Rahadianti, Silvia Desi; Daniati, Eva (Nursing Case Insight Journal, 2023)
A Caesarean section is a medical procedure in which a baby is born through an incision in the abdominal wall and the wall of the uterus. This procedure is performed when the fetus weighs over 500 grams, and the uterus is in a condition that makes a vaginal birth difficult or dangerous. Post Caesarean section, patients often experience physical and physiological impacts, such as pain. The incision in the stomach and uterus for delivering the baby and placenta causes pain, which can be superficial and can result in the disconnection of fiber nerves and pressure from stitching. A case study was conducted to evaluate the effectiveness of the Benson relaxation technique in reducing pain in patients post Caesarean section. The descriptive method was used with a case study approach. The results showed a decline in pain scale after the Benson relaxation technique was applied 2-3 times a day for three consecutive days. Before the technique was applied, the patient's pain scale was 6 out of a range of 0-10 (medium pain), but after the technique was applied for three days, the patient's pain reduced to a scale of 3 out of a range of 0-10 (light pain). This means that the Benson relaxation technique has been empirically proven to be an effective non-pharmacological treatment for reducing pain in patients post Caesarean section. It can be used as one of the non-pharmacological nursing interventions to overcome pain in patients post Caesarean section.